Use of Modern Information Technologies in English Lessons - Daminova Gulabza Ismatovna; Salakhitdinova Firuza Fazliddinovna; Pirimova Aziza Jurakulovna (International Journal on Integrated Education, 2022)
The use of games in English lessons is considered one of the most effective methods of teaching and developing the communicative competence of students. Studies show that its inclusion in education has a good effect on the process of mastering a foreign language, increases motivation, and improves speaking skills and fluency, orientation in real language situations.